Adverse event reports of anaphylaxis after Comirnaty and Vaxzevria COVID‐19 vaccinations, Western Australia, 22 February to 30 June 2021. Issue 2 (23rd February 2023) - Shivarev, Alexander; Phillips, Anastasia; Brophy‐Williams, Sam; Ford, Tim; Richmond, Peter; Effler, Paul; McLean‐Tooke, Andrew
Abstract: Within the first 4 months of the Western Australian COVID‐19 immunisation programme, 49 suspected anaphylaxis cases were reported to the vaccine safety surveillance system. Twelve reports met Brighton Collaboration case definition, corresponding to rates of 15.9 and 17.7 per million doses of Vaxzevria and Comirnaty administered respectively.